Real-world quantum sensors: evaluating resources for precision measurement. - Thomas-Peter, N; Smith, B; Datta, A; Zhang, L; Dorner, U; Walmsley, I (2011)
Quantum phenomena present in many experiments signify nonclassical behavior, but do not always imply superior performance. Quantifying the enhancement achieved from quantum behavior needs careful analysis of the resources involved. We analyze the case of parameter estimation using an optical interferometer, where increased precision can in principle be achieved using quantum probe states. Common performance measures are examined and some are shown to overestimate the improvement. For the simplest experimental case we compare the different measures and exhibit this overestimation explicitly. We give the preferred analysis of these experiments and calculate benchmark values for experimental parameters necessary to realize a precision enhancement. Our analysis shows that unambiguous real-world enhancements in optical quantum metrology with fixed photon number are yet to be attained.